2015
DOI: 10.7763/joebm.2015.v3.229
|View full text |Cite
|
Sign up to set email alerts
|

Towards ICT Impact Framework: Private and Public Sectors Perspective

Abstract: Abstract-Growing ICT role and adaptation implies various attempts to understand what economic benefits ICT bring to private and public sectors. Private sector was deeply analyzes by various researchers; however ICT impact on public sector is not explored in deep. Paper analyzes ICT development preconditions as well as various perspectives towards ICT economic impact evaluation. Considering earlier research paper proposes conceptual ICT impact on private and public sectors assessment model. Index Terms-ICT impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
5
11
0
4
Order By: Relevance
“…The finding shows that 131 respondents (62.4%) had over 9 years of experience in using a computer at MPC and 45 respondents (21.4%) had used computers between 7 and 9 years. The results of this study are consistent with the study by Gatautis et al (2015) found that ICT skills are vital to the ICT industry and the entire economy. The ICT industry relies on highly educated scientists and engineers, while companies in all sectors need to implement new technologies and depend on skilled labor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding shows that 131 respondents (62.4%) had over 9 years of experience in using a computer at MPC and 45 respondents (21.4%) had used computers between 7 and 9 years. The results of this study are consistent with the study by Gatautis et al (2015) found that ICT skills are vital to the ICT industry and the entire economy. The ICT industry relies on highly educated scientists and engineers, while companies in all sectors need to implement new technologies and depend on skilled labor.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted by Kirkman (2000) example, a poor experience with ICT will result in users not wanting to use ICT in the future. The results of this study are consistent with the findings of Gatautis et al (2015) which states that approximately 20% of total employment in the modern economy can be classified as an ICT-skilled worker.…”
Section: Discussionsupporting
confidence: 91%
“…si bien las tic han repercutido en las sociedades modernas, existe una brecha digital entre los actores individuales y colectivos que tienen acceso y usan las nuevas tecnologías y aquellos que no (serrano y Martínez, 2003). 1 en lo que respecta a los actores colectivos específicamente, la implementación de las tic en la gestión pública y privada ha permitido obtener beneficios tangibles e intangibles que han afectado directamente en la eficiencia, calidad y transparencia organizacional (Gatautis et al, 2015;Zimmermann y Finger, 2005). la incorporación de tecnologías en la gestión se tiende a materializar en herramientas como intranets, mejoramiento en la gestión de correos, utilización de mensajería instantánea de diverso tipo, automatización de procesos y flujos de trabajo (workflows), aumento en la capacidad para la gestión de información y documentos, y el in cremento en la capacidad para analizar grandes volúmenes de datos de manera automatizada o semiautomatizada a través de minería de datos (datamining) (Pérez y Dressler, 2007;Zack, 1999).…”
Section: Introductionunclassified
“…Este amplio desarrollo teórico reciente suele distinguir entre el suministro de servicios digitales y la democracia electrónica (Barría et al, 2017;Criado, 2004;Prieto-Martín, 2012). El suministro de servicios digitales o e-servicios se puede definir como servicios informacionales provistos y consumidos a través de Internet o cualquier otro canal electrónico, donde se genera un proceso de co-creación entre los ciudadanos y la administración pública, dando origen, de esta forma, al valor público (Boyer et al, 2002;Gatautis et al, 2015). La e-democracia o democracia electrónica, por otro lado, se entiende como la incorporación de las TIC para apoyar procesos democráticos de toma de decisiones, generando una ampliación de estos con base en las nuevas tecnologías (Barría et al, 2017;Saebø et al, 2008;Vicente y Novo, 2014).…”
Section: Tic Y Gobierno Electrónicounclassified
“…Si bien las TIC han impactado en las sociedades modernas, existe una brecha digital entre los actores individuales y colectivos que tienen acceso y usan las nuevas tecnologías y aquellos que no (Serrano y Martínez, 2003) 1 . En lo que respecta a los actores colectivos específicamente, la implementación de las TIC en la gestión pública y privada ha permitido obtener beneficios tangibles e intangibles que han impactado directamente en la eficiencia, calidad y transparencia organizacional (Gatautis et al, 2015;Zimmermann y Finger, 2005). La incorporación de tecnologías en la gestión se tiende a materializar en herramientas como intranets, mejoramiento en la gestión de correos, utilización de mensajería instantánea de diverso tipo, automatización de procesos y flujos de trabajo (workflows), aumento en la capacidad para la gestión de información y documentos, o el incremento en la capacidad para analizar grandes volúmenes de datos de manera automatizada o semi-automatizada a través de minería de datos (datamining) (Pérez y Dressler, 2007;Zack, 1999).…”
Section: Introductionunclassified